1986
DOI: 10.1111/j.1467-9892.1986.tb00481.x
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the Threshold Ar(1) Model With Cauchy Innovations

Abstract: A threshold autoregressive process of the first order with one threshold r and with Cauchy innovations is investigated in the paper. An explicit formula for the stationary density of such process is derived for the special case that r = 0 and that the autoregressive parameters have the same absolute value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 5 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…See Tong (1990) for a thorough review of results for the more general TAR models. Explicit formulae for the stationary solutions of such simple TAR models have been found when the noise distributions are normal, Cauchy and Laplace (Andel and Barton, 1986;Andel et al, 1984;Loges, 2004). More specifically, when = − , for the simplest TAR model with t a standard normal white-noise process, Andel et al (1984) have shown that its stationary distribution is of the form…”
Section: Connection Between the Simplest Tar Model And Sn Distributionsmentioning
confidence: 97%
“…See Tong (1990) for a thorough review of results for the more general TAR models. Explicit formulae for the stationary solutions of such simple TAR models have been found when the noise distributions are normal, Cauchy and Laplace (Andel and Barton, 1986;Andel et al, 1984;Loges, 2004). More specifically, when = − , for the simplest TAR model with t a standard normal white-noise process, Andel et al (1984) have shown that its stationary distribution is of the form…”
Section: Connection Between the Simplest Tar Model And Sn Distributionsmentioning
confidence: 97%
“…The Seasonal and Cyclical Long Memory (SCLM ) filter is defined by convolution. Any of the factors in (8) may be expanded as a binomial series given by Anděl et al (1986):…”
Section: Gegenbauer Arfisma-sαs Processmentioning
confidence: 99%
“…While there is an extensive study on obtaining explicit forms of the stationary marginal densities of such models (e.g. Anděl et al, ; Anděl and Bartoň, ; Chan and Tong, ; Loges, ), little work has been done to characterize them. By and large, our current work is intended to link the stationary marginal densities of certain MSETAR models to the skew‐symmetric densities (Genton, ; Azzalini and Capitanio, ) and to characterize them under certain additional but fairly broad assumptions.…”
Section: Introductionmentioning
confidence: 99%